AMAR MA’RUF NAHYI MUNKAR: ANALISIS SEMIOTIK DALAM FILM SERIGALA TERAKHIR - Fakhiroh, Zakiyatul (Fakultas Dakwah IAIN Purwokerto, 2011)
The rapid development in this modern era has made people develop the concepts of da'wah in many ways. The condition of people challenges the agents of da'wah acfivities to deliver Islamic values to reach the peaceful and prosperous condition of human beings. This article discusses the progress of da'wah activities which areconducted notonlythrough leduring but also through films. One of the films is Srigala Terakhir, which contains the value of inviting people for virfue and preventing them from doing bad things (amar ma'ruf nahi munkar). The values contained in the film have made its viewers give a respond as one of the responds to da'wah values.